Career development and internship quality among UiTM mathematics / Siti Rahimah Batcha, Nur Zafirah Mohd Sidek, Noratika Nordin, Harliza Hanif, Sumarni Abu Bakar, Zubaidah Sadikin and Vincent Daniel David - Batcha, Siti Rahimah; Mohd Sidek, Noor Zahirah; Nordin, Noratika; Hanif, Harliza; Abu Bakar, Sumarni; Sadikin, Zubaidah; David, Vincent Daniel (Universiti Teknologi MARA, Terengganu, 2024)
The internship program a short program designed by the university to provide students with practical work experience in their field of study. It allows students to apply their knowledge and skills in a real-world setting, gain valuable insights into their chosen career path, and build professional connections. Thus, the evaluation of an internship program must include an evaluation of specific skills that the students have for them to sustain in the professional sector. To ensure that students are fully ready to venture into the industry, there is an urgency to look into what skills they have mastered during their internship program. Thus, this study aims to identify the skill based on selected attributes (skills) namely thinking and scientific skills, communication skills, social skills, teamwork and responsibility, ethical values and professionalism, and information management and life-long learning. The study involved 257 Mathematics students who underwent an internship program and the data was analyzed using descriptive analysis. The result shows that UiTM Mathematics students excel during their internship program based on the five attributes that indicate the readiness of the student to develop their career in the industrial sector. Mostly the students can build skills and knowledge through the program continuously which gives them a good internship quality for their career development. Further analysis reveals that UiTM Mathematics students are among those to be offered as employees, particularly in the National private sector.